2018
DOI: 10.1007/s10047-018-1041-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of improved navigation performance on the accuracy of implant placement in total hip arthroplasty with a CT-based navigation system

Abstract: A computed tomography (CT)-based navigation system is one of the support tools to place implant with appropriate alignment and position in total hip arthroplasty (THA). To determine whether the higher performance of the navigation would further improve the accuracy of implant placement in the clinical setting, we retrospectively compared the navigation accuracy of two different versions of a navigation system. The newer version of the navigation system had an upgraded optical sensor with superior positional ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 39 publications
1
16
1
Order By: Relevance
“…The value of imageless navigation in avoiding radiation exposure has been reported [7,19]. The mean errors in inclination and cup anteversion with imageless navigation in THA were 6.8°and 3.7°, respectively [15]. Kalteis et al [19] reported that for patients with anatomical abnormalities such as acetabular dysplasia, imageless navigation imparted a number of disadvantages compared with CT-based navigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of imageless navigation in avoiding radiation exposure has been reported [7,19]. The mean errors in inclination and cup anteversion with imageless navigation in THA were 6.8°and 3.7°, respectively [15]. Kalteis et al [19] reported that for patients with anatomical abnormalities such as acetabular dysplasia, imageless navigation imparted a number of disadvantages compared with CT-based navigation.…”
Section: Discussionmentioning
confidence: 99%
“…CT-based navigation is useful for positioning implants in the correct alignment and orientation during THA, and newer navigation systems enable more accurate implant positioning [15]. CT-based navigation can help achieve correct cup orientation irrespective of operator experience [16].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as extensively demonstrated in human medicine (REF computer assisted vs freehand), computer assisted-surgeries could be more accurate and faster than free-hand techniques when performing osteotomy 13 fracture fixation 17 , joint replacement surgery 11 and vertebral screw placement as well 5 .…”
Section: Discussionmentioning
confidence: 95%
“…The value of imageless navigation in avoiding radiation exposure has been reported [7,19]. The mean errors in inclination and cup anteversion with imageless navigation in THA were 6.8º and 3.7º, respectively [13]. Kalteis et al [19] reported that for patients with anatomical abnormalities such as acetabular dysplasia, imageless navigation imparted a number of disadvantages compared with CTbased navigation.…”
Section: Discussionmentioning
confidence: 99%
“…CT-based navigation is useful for positioning implants in the correct alignment and orientation during THA, and newer navigation systems enable more accurate implant positioning [13]. CT-based navigation can help achieve correct cup orientation irrespective of operator experience [14].…”
Section: Discussionmentioning
confidence: 99%